2020
DOI: 10.2196/preprints.26433
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Suitability of Video Consultations During the COVID-19 Pandemic Lockdown: Cross-sectional Survey Among Norwegian General Practitioners (Preprint)

Abstract: BACKGROUND The COVID-19 pandemic imposed an acute, sharp rise in the use of video consultations (VCs) by general practitioners (GPs) in Norway. OBJECTIVE This study aims to document GPs’ experiences with the large-scale uptake of VCs in the natural experiment context of the pandemic. METHODS A nationwi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…A scoping review of experiences with VC in primary care, published in 2020, found a similar result in the general practice setting 3 . Despite this, the use of VC in general practice was low before the Covid-19 pandemic [4][5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A scoping review of experiences with VC in primary care, published in 2020, found a similar result in the general practice setting 3 . Despite this, the use of VC in general practice was low before the Covid-19 pandemic [4][5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…During the first Covid-19 lockdown, almost 90% of GP offices in Norway could offer VC 13 . Based on their initial experiences, Norwegian GPs envisioned substantial long-term use of VC 6 .…”
Section: Introductionmentioning
confidence: 99%